Doctor of Pharmacy in Jordan: Students’ Career Choices, Perceptions and Expectations - Nadine N. Abdelhadi; Mayyada Wazaify; Feras W. Darwish Elhajji; Iman A. Basheti (Journal of Pharmacy and Nutrition Sciences, 2014)
Purpose: To explore Jordanian Pharm.D students’ career choices, perceptions and expectations. Methods: This observational study was conducted during June 2013 at the University of Jordan. A total of 192 undergraduate Pharm.D students were invited to complete a questionnaire prepared and validated by the research team. The questionnaire investigated student’s demographics, the reasons behind choosing to study Pharm.D, satisfaction with the Pharm.D course, student’s future plans following graduation, and student’s perceptions about the Pharm.D specialty. Data collected were encoded and analyzed by SPSS database for Windows version17. Results:The majority (93%) of respondents was females,aspired to work as hospital clinical pharmacists (83%) and many (68%) believed that Pharm.D graduates are well respected by the general public. Results indicated that students are unaware of the current Pharm.D salaries and have higher expectations than what is being currently offered in the country. Conclusions:A generation of Pharm.D students from Jordan reported a future aspiration to work as hospital clinical pharmacists. Students have unrealistic salary expectations compared with the current salaries offered in Jordan. ‘Awareness workshops’ targeting students’ knowledge about the Pharm.D degree is required.